Of Pastorality in Petras Cvirka’s Works - Тетерина, Елена (Literatūra, 2016)
The article is devoted to the exposure and description of indications of pastoral figurativeness in Petras Cvirka’s literary works. In the author’s of this article opinion, the landscape description, pastoral chronotop, bucolic image, musical component have the character of semantic factors in some writer’s stories and the novel. These indications of pastorality not only organize the artistic world of Cvirka’s prose, but also demonstrate the stability and actuality of European pastoral traditions at the turning-point of history and convert his literary works from the tendentious field of urgent for his time ideas in the sphere of common to all mankind ontological meanings.